Mathematical Modeling of Security Forces – Insurgent Dynamics in Nigeria - O, Akpienbi Isaac; Adamu, Ibrahim Isa (Darul Yasin Al Sys, 2024)
In this study, a mathematical model of the dynamics of the interaction between Nigerian security forces and armed groups was developed. This model is based on demographic principles. When developing the model, the dynamics were conceptualized and structured along with the dynamics of predators and prey. The model developed was an analysis based on the Routh-Hurtwiz standard. The equilibrium points of the model were determined and their stability analysis was performed. The equilibrium factor is domestically asymptotically stable. In addition, we conducted numerical experiments to simulate the solution of the model. This study suggests that security agencies should be proactive in their response and improve their intelligence, peace building and weapons skills in combat conflicts in order to motivate security forces. Strengthen security forces and rehabilitation centers and improve rehabilitation programs for society as a whole.